Three new species of Australian miracine parasitoid wasps collected by regional schools as part of the Insect Investigators citizen science project (Hymenoptera, Braconidae, Miracinae) - Mollie-Rosae Slater-Baker; Michelle Guzik; Juanita Rodriguez; Andy Howe; Alice Woodward; Nathan Ducker; Erinn Fagan-Jeffries (Journal of Hymenoptera Research)
Miracinae is a poorly known and rarely collected subfamily of parasitoid wasps belonging to the family Braconidae. Here, three new species are described from material collected by Australian regional schools as part of the Insect Investigators citizen science project and named in collaboration with students: Mirax supremus Slater-Baker, sp. nov., Mirax ceduna Slater-Baker, sp. nov. and Mirax kaatijan Slater-Baker, sp. nov. The barcoding region of the cytochrome c oxidase subunit I (COI) gene was obtained for each new species and analysed alongside all publicly available COI DNA barcodes for Miracinae on the Barcode of Life Database, to produce a molecular framework to guide species delimitation and efficient morphological examination. Full morphological descriptions are provided along with high quality images for each new species. A key to described Australian Miracinae is provided.